PENGGUNAAN MEDIA GAMBAR DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS VI SD NEGERI I PEUSANGAN BIREUEN ACEH - Rahman, Aisyah A. (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2011)
This research was aimed to identify the differences and influences of pictorial media to the achievement of tenth grade students in Public Elementary School 1 Peusangan Bireuen Aceh, in the material ofÂ natural appearance and social condition in Neigborhoud Countries. The method used in this research was quasi experiment, i.e. a method to identify the influence of other variables to a specific variable. Two variables were analyzed in this research: (1) pictorial media as independent variable, and (2) studentsâ€™ achievement as dependent variable. Analysis resulted in a significant influence of pictorial media to studentsâ€™ achievement in geographic. It was showed by the value of t = 2.811 and two-tailed significance of 0,006, which resulted in p 0,05. Based on this result, it was decided that Ho cannot be accepted and H1 is accepted. Thus, it was concluded that there is a significant difference between students learning using pictorial media and students learning without pictorial media (focused on text book only).Key words: Pictorial media, learning achievement